PENERAPAN MODEL ARGUMENT-DRIVEN INQUIRY UNTUK MENINGKATKAN KEMAMPUAN BERARGUMENTASI ILMIAH MAHASISWA PADA TOPIK KALOR - St. Mutia Alfiyanti Muhiddin; Agussalim Agussalim (Karst: Jurnal Pendidikan Fisika dan Terapannya, 2023)
Abstract: Argument-Driven Inquiry (ADI) is a learning model that can train scientific argumentation skills. The ADI model is applied to the topic “Heat” in the Matter and Energy course. The aim of this study is to determine the development of pre-service teachers’ scientific argumentation skills after implementing the ADI model. This research is a quasi-experimental with The Pretest-Posttest Nonequivalent Group Design. Data was collected through essay test of scientific argumentation skills. Findings indicated a significantly higher mean normalized gain of students’ scientific argumentation skills in Experimental Group who were instructed using ADI compared to students in Control Group who received traditional instruction. The mean normalized gain of scientific argumentation skills of students in Experimental Group is 0,69 (medium-level) and in Control Group is 0,38 (medium-level). Based on hypothesis testing, it shows that the increase in scientific argumentation skills of students who have learned using the ADI model is significantly higher than who have learned using guided inquiry model. Thus, it can be concluded that learning using the ADI model can further enchance students' scientific argumentation abilities.